(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: In this study, the two methods of myringoplasty (underlay and over-underlay technique) were compared. Methods: Total 100 patients of COM (inactive mucosal variety) were studied for 06 months duration from 1st Oct 2015 to 31st March 2016 in the Dept of ENT & Head Neck Surgery, CMH Dhaka. The diagnosed cases of COM patients were selected according to the eligibility criteria’s by purposive sampling. 100 patients were equally divided into two groups. Patients in group1 underwent underlay method and patients in group 2 underwent over-underlay technique of myringoplasty. Patients were followed up for 6 months. Results: Graft uptake and hearing improvement was compared in both groups. In group 1 (underlay myringoplasty) graft taken rate was 92% and graft failure rate was 8%. In group 2 (Over-underlay myringoplasty) graft taken rate was 94% and failure rate was 6%. Graft uptake was 2% lower in the group1 than group 2 .The gain in hearing threshold (gain in A-B gap) in the group 1 (underlay myringoplasty) was (23.74 dB ± 3.97) and in group 2 )over-underlay myringoplasty) was (23.64 dB ± 4.03) Conclusion: The present study emphasizes the fact that there is no significant difference in short term results between the two techniques (underlay and over-underlay). Bangladesh J Otorhinolaryngol; October 2017; 23(2): 133-139